Quality analysis of teacher-made tests in financial accounting subject at vocational high schools - Heni Mulyani; Heraeni Tanuatmodjo; Rangga Iskandar (Jurnal Pendidikan Vokasi, 2020)
Assessment of student learning outcomes needs to be done using tests that meet the criteria for quality tests. This study aims to determine the quality of teacher-made tests on financial accounting subjects in Vocational High Schools. This research is descriptive research with a quantitative approach. Data collected are questions made by 32 teachers, answer sheets from 689 Accounting students. The validity of objective and essay tests using product-moment correlation. Reliability of the objective test using the KR20 formula, while the essay test using Alpha formula. Difficulty level and distinguishing power of objective tests using Anates 4. Difficulty level and distinguishing power of essay tests used Microsoft Excel 2013. The research results obtained are as follows: (1) validity of teacher-made test items cannot accurately measure learning outcomes; (2) reliability of teacher-made tests cannot show stable results despite repeated testing of the same subject; (3) teacher-made tests do not have a proportion of degree of difficulty that is suitable for use as a Mid-Semester assessment tool; (4) distinguishing power of tests made by teachers cannot distinguish students who have mastered the test material (upper or superior group) from students who have not mastered the test material (lower group or user); (5) Multiple choice test distractors made by teachers are not evenly chosen, and the key options and deception options do not function effectively. Quality analysis of teacher-made tests through item analysis is intended to identify damaged test items and to show areas that are already mastered by students.